Ambivalence in psychotherapy questionnaire: development and validation studies - Oliveira, João Tiago (2020)
Research emphasizes that individuals' engagement with change process is a significant predictor of therapeutic outcomes. Ambivalence is a natural phenomenon in change processes, but when individuals cannot overcome it, their problems may intensify. Ambivalence towards change, a client variable characterized by an intrapersonal conflict between two positions of the self, one in favour of change and another one in favour of the status quo, is shown to play a determinant role in psychotherapy. Despite its importance, few empirical studies have examined this process, and the considerable methodological differences among existing studies make it difficult to generalize results. Therefore, instruments measuring ambivalence in an effective way can help broaden the understanding of the process. First, we performed a content analysis of ambivalence events identified in psychotherapy sessions from previous studies using an observational coding system. The factor structure, reliability and validity of the measure were tested using 91 and confirmed with 223 psychotherapy clients at any time during the therapeutic process. A two-factor structure was found, suggesting two components of Ambivalence-Demoralization and Wavering. The results indicated that the Ambivalence in Psychotherapy Questionnaire exhibits good psychometric properties, including good convergent and divergent validity. The implications are discussed.